Knowledge, attitudes, and beliefs about HIV/AIDS and people living with HIV among medical students at Qassim University in Saudi Arabia - Alawad, Moayad; Alturki, Abdulkarim; Aldoghayyim, Abdullah; Alrobaee, Abdulmalik; Alsoghair, Mansour (International Journal of Health Sciences, 2019)
Background: Human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS) is a global health problem. Since Saudi Arabia is becoming more open to the world, it is important to assess future doctors’ knowledge, attitudes, and practices (KAPs) regarding HIV/AIDS and people living with HIV (PLHIV). Materials and Methods: This cross-sectional study included 204 male medical students of Qassim University who answered a self-administered questionnaire about HIV KAPs. Results: The mean HIV knowledge (HK) and attitude scores were 11.62 (64.5%) and 37.82 (67.5%), respectively. Positive correlations were observed between HK and attitude (r = 0.266) and HK and academic year (r = 0.277). No significant correlation was found between attitude and academic year (r = 0.097). More than half of the students exhibited ignorance about some modes of transmission such as deep kissing and vertical transmission. Around 81% of the students stated that they would not visit the homes of friends with HIV-infected members. Furthermore, 73.1% of the participants indicated that they would not provide care to HIV-positive relatives in their own homes. Conclusions: The findings show a modest level of HK and negative attitudes toward PLHIV. The study identified the main knowledge gaps in the transmission and prevention of HIV. Educational institutions should tailor their educational approach based on the identified gaps, which might help to ease the stigma and negative attitudes.